2017
DOI: 10.1093/mnras/stx1062
|View full text |Cite
|
Sign up to set email alerts
|

Radio and optical intra-day variability observations of five blazars

Abstract: We carried out a pilot campaign of radio and optical band intra-day variability (IDV) observations of five blazars (3C66A, S5 0716+714, OJ287, B0925+504, and BL Lacertae) on December 18-21, 2015 by using the radio telescope in Effelsberg (Germany) and several optical telescopes in Asia, Europe, and America. After calibration, the light curves from both 5 GHz radio band and the optical R band were obtained, although the data were not smoothly sampled over the sampling period of about four days. We tentatively a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…For sources at cosmological distances, the velocity of the pattern is essentially that of the screen (Cordes & Rickett 1998), and therefore the change in the velocity of the Earth as it orbits the Sun can strongly affect the variation timescales. This annual modulation has so far been reported in a handful of sources: J1819+3845 (Dennett- Thorpe & de Bruyn 2001, 2003; QSO B0917+624 (Jauncey & Macquart 2001;Rickett et al 2001;Fuhrmann et al 2002); PKS 1257−326 ; PKS B1519−273 (Jauncey et al 2003); PKS B1622−253 (Carter et al 2009); S5 0716+714 ); 0925+504 (Liu & Liu 2015;Liu et al 2017); S4 0954+65 ; 1156+295 (4C+29.45, Liu et al 2013; and J1128+5925 (Gabányi et al 2007b,a). Together with the two-station experiments (Dennett- Thorpe & de Bruyn 2002;Bignall et al 2006), which directly demonstrated the existence of a spatial flux pattern, the annual cycles provided the key evidence that proved IDV to be scintillation.…”
Section: Introductionmentioning
confidence: 62%
“…For sources at cosmological distances, the velocity of the pattern is essentially that of the screen (Cordes & Rickett 1998), and therefore the change in the velocity of the Earth as it orbits the Sun can strongly affect the variation timescales. This annual modulation has so far been reported in a handful of sources: J1819+3845 (Dennett- Thorpe & de Bruyn 2001, 2003; QSO B0917+624 (Jauncey & Macquart 2001;Rickett et al 2001;Fuhrmann et al 2002); PKS 1257−326 ; PKS B1519−273 (Jauncey et al 2003); PKS B1622−253 (Carter et al 2009); S5 0716+714 ); 0925+504 (Liu & Liu 2015;Liu et al 2017); S4 0954+65 ; 1156+295 (4C+29.45, Liu et al 2013; and J1128+5925 (Gabányi et al 2007b,a). Together with the two-station experiments (Dennett- Thorpe & de Bruyn 2002;Bignall et al 2006), which directly demonstrated the existence of a spatial flux pattern, the annual cycles provided the key evidence that proved IDV to be scintillation.…”
Section: Introductionmentioning
confidence: 62%
“…Its mean flux density is slightly increased from session 1 to session 2. The blazar has previously shown fast IDV with Urumqi 25 m and Efferlsberg 100 m telescope, its IDV timescales can be fitted with the annual modulated ISS model [36,37].…”
Section: Comment On Individual Sourcesmentioning
confidence: 99%
“…Mostly, observations at centimeter and meter wavelengths have dominant extrinsic variability, which is due to interstellar scintillation of radio waves caused by the turbulent interstellar medium of the Milky Way, while IDV are in the millimeter wavelength of the intrinsic origin. Radio IDV studies of blazars were pioneered by the 100-m Effelsberg radio telescope in Germany, as well as other radio and mm wavelength telescopes (e.g., [17,25,102,[111][112][113][114][115][116][117][118][119][120][121]; and the references therein).…”
Section: Idv In Radio Bandsmentioning
confidence: 99%
“…IDV was detected in all three radio frequencies, and it was also noticed that low and high frequency correlations do not peak at zero lag, which shows that low frequency radio observation is the combined effect of an intrinsic and an extrinsic mechanism. Optical and radio IDV observations were carried out by [121]. IDV observation along with VLBI analysis was carried out for the blazar S4 0917+624 [120].…”
Section: Idv In Radio Bandsmentioning
confidence: 99%